The point-slope form of the equation of a line is given by the formula:
\[ y - y_1 = m(x - x_1) \]
where \( m \) is the slope of the line, and \( (x_1, y_1) \) is a point on the line.
Given the slope \( m = 2 \) and the point \( (x_1, y_1) = (-5, 4) \), we can substitute these values into the point-slope form:
\[ y - 4 = 2(x - (-5)) \]
This simplifies to:
\[ y - 4 = 2(x + 5) \]
So, the point-slope form of the equation of the line is:
\[ y - 4 = 2(x + 5) \]
In the format you provided:
- \( y - 4 \) corresponds to \( y - \)
- \( 2 \) corresponds to the slope
- \( x - (-5) \) corresponds to \( x - \)
Thus:
- The complete answer is:
\[ y - 4 = 2(x + 5) \]